Integral Use of Amaranth Starch to Obtain Cyclodextrin Glycosyltransferase, by Bacillus megaterium, to Produce β-Cyclodextrin - Arce-Vázquez, María Belem; Ponce-Alquicira, Edith; Delgado-Fornué, Ezequiel; Pedroza-Islas, Ruth; Díaz-Godínez, Gerardo; Soriano-Santos, J. (Frontiers in Microbiology, 2016)
Cyclodextrin glycosyltransferase (CGTase) is an enzyme that produces cyclodextrins (CDs) from starch and related carbohydrates, producing a mixture of α-, β-, and γ-CDs in different amounts. CGTase production, mainly by Bacillus sp., depends on fermentation conditions such as pH, temperature, concentration of nutrients, carbon and nitrogen sources, among others. Bacillus megaterium CGTase produces those three types of CDs, however, β-CD should prevail. Although waxy corn starch (CS) is used industrially to obtain CGTase and CDs because of its high amylopectin content, alternative sources such as amaranth starch (AS) could be used to accomplish those purposes. AS has high susceptibility to the amylolytic activity of CGTase because of its 80% amylopectin content. Therefore, the aim of this work was evaluate the AS as carbon source for CGTase production by B. megaterium in a submerged fermentation. Afterwards, the CGTase was purified partially and its activity to synthesize α-, β- and γ-CDs was evaluated using 1% AS as substrate. B. megaterium produced a 66 kDa CGTase (Topt=50°C; pHopt=8.0), from the early exponential growth phase which lasted 36 h. The maximum CGTase specific activity (106.62±8.33 U/mg protein) was obtained after 36 h of culture. CGTase obtained with a Km=0.152 mM and a Vmax=13.4 µM/min yielded 40.47% total CDs using AS which was roughly twice as much as that of corn starch (CS; 24.48%). High costs to produce CDs in the pharmaceutical and food industries might be reduced by using AS because of its higher α-, β- and γ-CDs production (12.81%, 17.94% and 9.92%, respectively) in a shorter time than that needed for CS.